INSTRUCTIONAL DESIGN FOR MULTIMEDIA: STRATEGIES TO ENHANCE LEARNING IN THE CONTEXT OF EMERGING TECHNOLOGIES (Editora Impacto Científico, 2025)
This study investigated how instructional design strategies can be improved to enhance learning in multimedia environments within the context of emerging technologies. The research stemmed from the need to understand how digital resources, when pedagogically planned, can make the educational process more effective, inclusive, and meaningful. The general objective was to understand how instructional design strategies can be enhanced to foster learning in multimedia settings, analyzing the impact of emerging technologies on retention, engagement, and accessibility in education. The methodology adopted was bibliographic research, analyzing scientific publications from 2015 to 2025, selected from reputable databases such as the Scientific Electronic Library Online (Scielo) and Google Scholar. The results revealed that the intentional use of multimedia resources contributes to creating more engaging educational experiences, especially when combined with adaptive platforms, gamification, augmented reality, and hybrid teaching strategies. Furthermore, it was found that instructional design practices based on accessibility principles promote greater equity in the educational process, benefiting students with diverse profiles and needs. Among the main challenges identified are the need for teacher training, limited access to technology in certain contexts, and the demand for intentional planning to avoid the superficial use of resources. It is concluded that instructional design, when integrated with emerging technologies, is a powerful tool for transforming education and preparing students for contemporary challenges.